Subjective and Objective Evaluation Of Physical Activity Level And Its Relationship With Work Ability Of Nurses In Different Hospital Departments - Rastimehr, Mahdieh; Mazloumi, Adel; Kazemi, Zeinab; Chalak, Mohammad Hossein (La Medicina del Lavoro, 2025)
Background: Due to the nature of shift work, nurses experience very high mental and physical pressure, which can ultimately affect their work ability (WA). One factor that affects work ability is the level of physical activity (PAL). Since nurses are responsible for providing healthcare for the public, it is necessary to evaluate their WA and PAL. Therefore, the present study used subjective and objective evaluation to test the relationship between PAL and WA among nurses in different hospital departments affiliated with Isfahan University of Medical Sciences. Methods: A descriptive-analytical study was conducted over 6 months. A questionnaire was used to measure the work ability index (WAI). The International Physical Activity Questionnaire (IPAQ) was used for subjective evaluation, and the Xiaomi smart wristband Mi Band Five was used for objective assessment. These tools extracted the components of behaviors related to physical activity for 7 days. One hundred nurses were selected for subjective evaluation, and then 40 of them were randomly selected for objective assessment. The SPSS software version 23 was used for data analysis. Multiple regression analysis was used to test the effect of physical activity on the work ability index by controlling other demographic variables. Results: 7% of participants had poor WAI, and 45% had moderate work ability. Also, the ability to do good and excellent work was 32% and 16%, respectively. In this study, 31% of participants had low PAL, 42% moderate PAL, and 27% high PAL. In the objective evaluation, 12.5% of participants had a PAL of 100, 35% less than 100(poor), and 52.5% had a PAL above 100(High). In the subjective evaluation, the highest PAL belonged to the emergency department. The results of the subjective and objective methods to check the correlation between WAI and PAL showed a positive and significant correlation. Conclusion:In the present study, subjective and objective evaluations showed a significant relationship between work ability and PAL. The present findings can be used to develop future interventions to improve nurses' health and work performance.